Central China Orogen along the Silk Road (Part I): Tectono‐thermal evolution and its links. (30th December 2017) - Li, Sanzhong; Suo, Yanhui; Yu, Shengyao; Li, Rongxi; Yang, Gaoxue; Somerville, I.D.
Abstract : This Special Issue volume on the Central China Orogen includes 35 papers involving the geology along the Ancient Silk Road in China. All the papers focus on tectono‐thermal evolution and its links.